2021
DOI: 10.54386/jam.v23i2.70
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of aphid complex and its associated natural enemies in rapeseed-mustard in relation to climatic factors

Abstract: Effect of climatic factors on population build-up of aphid complex of rapeseed-mustard viz. mustard aphid, Lipaphis erysimi (Kaltenbach), cabbage aphid, Brevicoryne brassicae (Linnaeus), and green peach aphid, Myzus persicae (Sulzer) and associated natural enemies (coccinellids, syrphids and a parasitoid, Diaeretiella rapae M’Intosh) was studied at Experimental Farm of CSK HPKV Palampur over a period of three years. Correlation coefficients indicated that the temperature favoured build-up of aphid popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Samples were randomly collected from 50 plants, and observations on the aphid population were recorded at fortnightly intervals separately for L. erysimi , B. brassicae , and M. persicae . Simultaneously, observations on the population of coccinellids (total number of adults and grubs/plant) and syrphids (total number of maggots/10 cm apical twig) were recorded as per the methodology of Soni et al (2021). Parasitization (%) by Diaeretiella rapae was worked out by directly counting the number of mummified and healthy aphids at the time of recording aphid population as per the method of Root and Skelsey (1969):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were randomly collected from 50 plants, and observations on the aphid population were recorded at fortnightly intervals separately for L. erysimi , B. brassicae , and M. persicae . Simultaneously, observations on the population of coccinellids (total number of adults and grubs/plant) and syrphids (total number of maggots/10 cm apical twig) were recorded as per the methodology of Soni et al (2021). Parasitization (%) by Diaeretiella rapae was worked out by directly counting the number of mummified and healthy aphids at the time of recording aphid population as per the method of Root and Skelsey (1969):…”
Section: Methodsmentioning
confidence: 99%
“…are important and inflict around 90% crop yield losses (Sharma and Kashyap 1998). Soni et al (2021) reported that B. brassicae and L. erysimi are the most abundant among all insects infesting rapeseed–mustard in Palampur, Himachal Pradesh.…”
Section: Introductionmentioning
confidence: 99%